THE ROLE OF MUSIC IN PERSONAL DEVELOPMENT (American Journal of Pedagogical and Educational Research, 2023)
This article provides detailed information about the methods of music teachers in the lessons of music culture, the skills of students and the basic knowledge of vocal singing.